Penerapan Model Pembelajaran Kooperatif Tipe Snowball Throwing Terhadap Pemahaman Konsep Matematis Siswa Kelas III SDN 3 Menduran - Ira Afriani; Muhammad Arif (Algebra: Journal of Matematics, Statistics and Computation, 2024)
This study aimed to enhance students' understanding of mathematical concepts in Grade III at SDN 3 Menduran by implementing the Snowball Throwing cooperative learning model. It employed a qualitative descriptive research design. The population consisted of all 16 Grade III students at SDN Menduran. Research instruments included essay tests and interviews. Test results were analyzed based on concept comprehension indicators. The research findings indicated that the overall qualification score for mathematical concept comprehension among the 16 tested students was 75%, which falls into the high category. This signifies an improvement from an initial comprehension level of only 44%. Students demonstrated positive qualification scores in specific indicators of mathematical concept comprehension. They exhibited high levels of understanding in several indicators, such as restating a concept (81%), developing necessary or sufficient conditions of a concept (81%), and applying concepts or problem-solving algorithms (94%).Indicators needing further attention included classifying objects according to their concepts, which scored low (50%). The indicator of providing examples and non-examples of concepts and presenting concepts in mathematical representations were moderate (75%). In conclusion, this research suggests that the Snowball Throwing cooperative learning model effectively enhances Grade III students' understanding of mathematical concepts at SDN 3 Menduran.